Commerce in Nigeria 1966: Volume 8 - Lagos Chamber of Commerce and Industry (Lagos: Lagos Chamber of Commerce and Industry, 1966)
This is the 1966 edition of the Commerce in Nigeria, a publication of the Lagos Chamber of Commerce and Industry which provides an annual examination the Nigerian economy. This edition covers: the Nigerian economy-performance and prospects; the Nigerian refinery; developments in Architecture in Lagos; Telecommunications in Nigeria; Tobacco-a growing industry; classified business directory and an index of advertisers.
lje 21/1/19
Loans
Keywords: Commerce; Commerce; Nigeria